1998
DOI: 10.1073/pnas.95.5.2244
|View full text |Cite
|
Sign up to set email alerts
|

Junction ribonuclease: An activity in Okazaki fragment processing

Abstract: The initiator RNAs of mammalian Okazaki fragments are thought to be removed by RNase HI and the 5-3 f lap endonuclease (FEN1). Earlier evidence indicated that the cleavage site of RNase HI is 5 of the last ribonucleotide at the RNA-DNA junction on an Okazaki substrate. In current work, highly purified calf RNase HI makes this exact cleavage in Okazaki fragments containing mismatches that distort the hybrid structure of the heteroduplex. Furthermore, even fully unannealed Okazaki fragments were cleaved. Clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 29 publications
2
82
2
Order By: Relevance
“…Because these polymerases do not have intrinsic dRPase activity, the 5′ terminus at the cleavage site needs to be cleaned up by an endo (or exo) nuclease. One obvious candidate is the flap endonuclease (FEN1), a paralog of the 5′-exonuclease activity intrinsic to Escherichia coli DNA polymerase I. FEN1 is normally involved in removal of the 5′-RNA primers of nascent Okazaki fragments during DNA replication [Murante et al, 1998]. In vitro reconstitution experiments showed that FEN1 can remove the dRP residue, along with several additional residues, from the 5′ terminus [Gary et al, 1999].…”
Section: Long Patch Vs Short Patch Repair Synthesis In Bermentioning
confidence: 99%
“…Because these polymerases do not have intrinsic dRPase activity, the 5′ terminus at the cleavage site needs to be cleaned up by an endo (or exo) nuclease. One obvious candidate is the flap endonuclease (FEN1), a paralog of the 5′-exonuclease activity intrinsic to Escherichia coli DNA polymerase I. FEN1 is normally involved in removal of the 5′-RNA primers of nascent Okazaki fragments during DNA replication [Murante et al, 1998]. In vitro reconstitution experiments showed that FEN1 can remove the dRP residue, along with several additional residues, from the 5′ terminus [Gary et al, 1999].…”
Section: Long Patch Vs Short Patch Repair Synthesis In Bermentioning
confidence: 99%
“…Several nucleases, including RNase H2, Rad27/ FEN1, and Dna2, have been implicated in the processing of the 5= ends of Okazaki fragments (2)(3)(4). RNase H2 is an endonuclease that degrades the RNA strand of RNA/DNA hybrids by cleaving the 5= end of RNA phosphodiester bonds (5)(6)(7)(8). RNase H2 is comprised of three subunits that are encoded by the genes RNH201 (formerly known as RNH35), RNH202, and RNH203 in Saccharomyces cerevisiae (9) and the genes RNASEH2A, RNASEH2B, and RNASEH2C in humans (10).…”
mentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, as in mammalian cells, removal of the RNA primer is thought to be mediated by an endo/exonucleolytic activity called FEN-1 (flap endonuclease or 5Ј-exonuclease 1 [20,21]), presumably aided by RNase H1 (18,24,36,48,50; for reviews, see references 17, 29, and 32). Recent biochemical analyses of the FEN-1 nuclease indicate that the FEN-1 protein interacts with, and its activity is stimulated by, PCNA (31,56).…”
mentioning
confidence: 99%